Human corridors safe in international humanitarian law - الطبطش , الصادق; احمد مصباح على, اشرف احمد مصباح على; بلحارث, سعيد بلحارث (Sharwes Scientific Journal, 2025)
The research covers the governing principles for the safe humanitarian corridor during armed conflicts whether they were international conflicts or local conflicts. or local conflicts .the importance of this research lies within to create humanitarian corridors we can find answers to all of this in general principles the legal rules and the international law which  aims  to protect civilians as well as those who  are not involved in the conflict save their lives provide humanitarian assistance to safe areas away from conflicts zone.